1995
DOI: 10.1111/j.1365-2591.1995.tb00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic preparation and obturation of root‐end cavities

Abstract: This study evaluated the preparation of root-end cavities using an ultrasonically activated file, and the obturation of such cavities. In the first part, the root canals of 40 extracted teeth were prepared to size 40 and irrigated with NaOCl and EDTA. The root ends were resected and the teeth inoculated with Enterococcus faecalis, incubated for 10 days and divided into four groups: control; saline; irrigation; hand instrumentation performed via a retrograde approach up to size 50 using saline irrigant; ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Wuchenich et al (1994) showed that root-end cavities prepared using ultrasonic tips were deeper, had parallel walls and followed the long axis of the root canal system compared with those prepared by burs. In another study, when retrograde instrumentation was carried out on teeth using an ultrasonically-activated file, it was reported that at the root end, there was a significant reduction in the quantity of bacteria, which had previously been inoculated (Sultan & Pitt Ford 1995). It may be argued that if ultrasound had been used, the results of this study might have been better.…”
Section: Discussionmentioning
confidence: 73%
“…Wuchenich et al (1994) showed that root-end cavities prepared using ultrasonic tips were deeper, had parallel walls and followed the long axis of the root canal system compared with those prepared by burs. In another study, when retrograde instrumentation was carried out on teeth using an ultrasonically-activated file, it was reported that at the root end, there was a significant reduction in the quantity of bacteria, which had previously been inoculated (Sultan & Pitt Ford 1995). It may be argued that if ultrasound had been used, the results of this study might have been better.…”
Section: Discussionmentioning
confidence: 73%
“…The cleaning effect and the cutting ability of ultrasonic retrotips have been described as satisfactory by many authors (222,223,233,237,249,250). Furthermore, US produced less smear layer in a retro-end cavity compared to a slow-speed handpiece (214,221,(233)(234)(235)251).…”
Section: Surgical Endodontics: Root-end Cavity Preparation and Refinementioning
confidence: 91%
“…Ultrasonic retrotips have been developed as an alternative to the low‐speed handpiece for root‐end cavity preparation. Many reports have been written on the properties of ultrasonic retrotips (Gorman et al . 1995, Sultan & Pitt Ford 1995, Frank et al .…”
Section: Introductionmentioning
confidence: 99%